Conceito, proteção ambiental e morfogênese de chapadas no Brasil - MARTINS, Fernanda Pereira (2018)
The tablelands are common landforms in brazilian landscapes. Sometimes they occur in isolation, but can also occur in a grouping of these geoforms.. The Brazilian Institute of Geography and Statistics (IBGE, 2006) classified eight brazilian units of relief as tableland areas. They are concentrated in the northeast, southeast and, in a lesser extent, in the Midwest. From the moment that legislation (Código Florestal Lei no 12.651/2012 and the Resolução Conama nº 303/2002) established the tablelands edges as Permanent Protection Area, these geoforms were legally recognized as possessing great environmental importance. However, despite this recognition, the tablelands still lack scientific studies. In this sense, this researche is structured on three guiding principles: (i) discuss the legal concept of tableland in Brazil; (ii) make a scientific concept of tableland form and and; (iii) understand the typical morphodynamics of this landscapes in two representative areas of tablelands in Brazil: (A) the region called Chapada das Mesas in the state of Maranhão and Tocantins and (B) the south portion of the Chapadas do Rio São Francisco, Minas Gerais State. To achieve the proposed objectives, it was first analysed if the eight units classified as tablelands by IBGE (2006) meet all the parameters required by legislation: tableland surface slope, slope of their edges, surface extension and altitude. Afterwards, 22 specialists in geomorphology were consulted to use the Delphi method to determine the main parameters for classifying a geoform as being tablelands, as well as to create a scientific definition for this geoform and to see its adherence to reality of the eight tablelands relief units in Brazil (IBGE, 2006). Finally, it was tested in the two previous selected areas, if the parameters suggested in Delphi as typical of the tablelands genesis (processes) is applied to the reality of these geoforms. For that, field observation, geoprocessing and remote sensing methods was used, and, in the case of the Chapadas das Mesas, laboratory data of cosmogenic isotope Be10 was also used. It was concluded that the current legislation does not fulfill its objective to protect the tablelands because it uses a confusing and restrictive concept, not covering the actual occurrence of this type of relief in Brazil. By means of the Delphi method, it was possible to create a concept more compatible with the reality of the occurrence of these geoforms in Brazil and, therefore, it can be used by the legislation, contributing to the understanding of the natural evolutionary tablelands dynamics. With regard to morphogenesis, the analysis of the Chapadas das Mesas has shown that the morphogenetic processes were more heterogeneous than those mentioned in the geomorphological classics and than those raised in this work through the Delphi method. . In this area, karstic subsurface processes in non-carbonate rocks – siliciclastic - occurred in interaction with the surface processes of the supergene cycle. That is, typical karst processes were fundamental for the morphogenesis of plateaus in the Chapada das Mesas region. This fact is relevant, because up to the present time there was no mention in the geomorphological bibliographies of the karstic processes as precursors of the tablelands morphogenesis. The morphogenesis of the South of the Chapadas do Rio São Francisco unit has been shown to be in greater conformity with the morphogenesis described by the evolutionary theories of the long term landscape. The analysis of these two representative areas of tablelands demonstrated that they are polygenetic relief forms and should not be analyzed from a deductive perspective.